'Out with the Old?' Why coarse spatial datasets are still useful for catchment‐scale investigations of sediment (dis)connectivity. Issue 10 (27th March 2017) - Lisenby, Peyton E.; Fryirs, Kirstie A.
Abstract: The increasing popularity of remote sensing techniques has created numerous options for researchers seeking spatial datasets, especially digital elevation models (DEMs), for geomorphic investigations. This yields an important question regarding what DEM resolution is most appropriate when answering questions of geomorphic significance. The highest possible resolution is not always the best choice for a particular research aim, and DEM resolution should be tailored to fit both the scale of investigation and the simplicity/complexity of modelling processes applied to the dataset. We find that DEM resolution has a significant effect on a simple model of bed load sediment connectivity in the Lockyer Valley, Queensland. We apply a simple bed load transport threshold to catchment DEMs at three different resolutions – 1 m, 5 m, and 25 m. We find that using a 1 m resolution DEM generates numerous disconnections along tributary channel networks that underestimates the sediment contributing area, i.e. effective catchment area (ECA), of seven tributary basins of Lockyer Creek. Utilizing a coarser (lower‐resolution) DEM helps eliminate erroneous disconnections, but can reduce the detail of stream network definition. We find that the 25 m resolution DEM provides the best measure of ECA for comparing sediment connectivity between tributary catchments. The utility of simple models and coarse‐resolution datasets is important for undertaking large, catchment‐scale geomorphic investigations. As catchment‐scale investigations are becoming increasingly entwined with river management and rehabilitation efforts, scientists need not embrace an 'out with the old' philosophy. Simple models and coarse‐resolution datasets can help better integrate geomorphic research with management strategies and provide inexpensive and quick first‐order insights into catchment‐scale processes that can help focus future management efforts. Copyright © 2017 John Wiley & Sons, Ltd.